Pemanfaatan Teknologi Termal Dalam Pengolahan Sampah Plastik Menjadi Wood Plastic Composite (WPC) Sebagai Solusi Atas Pencemaran Lingkungan Akibat Limbah Plastik - Sabeta, Mafaza Nuris; Sudarti, Sudarti; Yushardi, Yushardi (Peneliti.net, 2024)
Plastic waste is an environmental problem that is very difficult to solve. To decompose it alone takes approximately 80 years for the plastic waste to decompose completely. In 2022, plastic waste will be the second most generated waste after food waste, which is 17.8% of all waste generated in Indonesia. Therefore, this research was made to overcome environmental problems due to plastic waste by utilizing thermal technology in the manufacture of Wood Plastic Composite (WPC). This research uses the literature study method by collecting several reading sources from previous research. In the utilization of thermal technology, several stages are carried out, namely washing, drying, chopping, then given thermal treatment, and the last is printing. the utilization of thermal technology in the processing of plastic waste into Wood Plastic Composite (WPC) is effective in reducing environmental pollution due to plastic waste. Processing plastic waste through thermal technology will increase the durability of Wood Plastic Composite (WPC) such as water resistance, color resistance to ultraviolet radiation, and this material is environmentally friendly. The utilization of thermal technology in converting plastic waste into Wood Plastic Composite (WPC) will help reduce the amount of plastic waste and reduce environmental pollution due to plastic waste.